Penerapan Model Pembelajaran Berbasis Proyek pada Mata Kuliah Strategi Pembelajaran Bahasa Indonesia sebagai Upaya Meningkatkan Hasil Belajar Mahasiswa Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Jambi 2021/2022 - Andiopenta Purba (Universitas Batanghari Jambi, 2023)
This study aims to describe the application of a project-based learning model to learning Indonesian language learning strategies. The research sample consisted of 30 control classes and 30 experimental classes of Indonesian Language Education Study Program students. Data collected by observation techniques, questionnaires, and tests. The data analysis technique used the percentage technique and t-test statistics via SPSS-23. In addition, a procedural analysis of the application of project-based learning through six steps is used. In addition, observations of student learning motivation reached an average of 86 in the experimental class and 78 in the control class. In terms of learning creativity it reached 87 for the experimental class and 76 for the control class. While the results of observations of student learning outcomes reached 85 for the experimental class and 74 for the control class. Thus the observation results show a higher rating in the experimental class when compared to the control class. The results of the different test between the control class and the experimental class showed a significant difference between the ttest and t-table, through the t-test namely on learning motivation learning motivation 6,629 > 1,686 learning creativity 6,758 > 1,686 and learning outcomes 6,762 > 1,686. Thus the research hypothesis; There is a significant difference between the control class and the experimental class in learning project-based Indonesian language learning strategies. Thus learning project-based Indonesian language learning strategies courses is proven to be able to increase learning motivation, learning creativity, and student learning outcomes. Research conclusion; Learning motivation, learning creativity and student learning outcomes in learning strategy courses can be improved through learning using project-based learning models for students of the Indonesian Language and Literature Education Study Program FKIP Jambi University odd semester 2021.2022. The process of implementing project-based learning models in Learning Strategy courses Indonesian for students of the Indonesian Language Education Study Program FKIP Jamabi University for the odd semester of 2021/2022 is taking place effectively. Implementation of project-based learning at every step of implementation starting from; determining questions, designing project plans, compiling schedules, monitoring students and project progress, testing results, and evaluating experiences goes well until students look very enthusiastic and excited. This can be seen from the observation categories which show good and very good categories